Artificial Muscles from Hybrid Carbon Nanotube‐Polypyrrole‐Coated Twisted and Coiled Yarns. Issue 11 (11th September 2020) - Aziz, Shazed; Martinez, Jose G.; Foroughi, Javad; Spinks, Geoffrey M.; Jager, Edwin W. H.
Abstract: Electrochemically or electrothermally driven twisted/coiled carbon nanotube (CNT) yarn actuators are interesting artificial muscles for wearables as they can sustain high stress. However, due to high fabrication costs, these yarns have limited their application in smart textiles. An alternative approach is to use off‐the‐shelf yarns and coat them with conductive polymers that deliver high actuation properties. Here, novel hybrid textile yarns are demonstrated that combine CNT and an electroactive polypyrrole coating to provide both high strength and good actuation properties. CNT‐coated polyester yarns are twisted and coiled and subjected to electrochemical coating of polypyrrole to obtain the hierarchical soft actuators. When twisted without coiling, the polypyrrole‐coated yarns produce fully reversible 25° mm ‐1 rotation, 8.3× higher than the non‐reversible rotation from twisted CNT‐coated yarns in a three‐electrode electrochemical system operated between +0.4 and –1.0 V (vs Ag/AgCl). The coiled yarns generate fully reversible 10° mm ‐1 rotation and 0.22% contraction strain, 2.75× higher than coiled CNT‐coated yarns, when operated within the same potential window. The twisted and coiled yarns exhibit high tensile strength with excellent abrasion resistance in wet and dry shearing conditions that can match the requirements for using them as soft actuators in wearables and textile exoskeletons. Abstract : Textile yarn‐based hybrid artificial muscles are developed that integrates the fundamental properties of carbon nanotubes and a conductive polymer. The twisted/coiled structured yarns generate both linear and torsional actuation under small electrochemical potential change. The developed muscles exhibit high tensile strength with excellent abrasion resistance that can match the requirements for using them as wearable smart textiles.